ChemInform Abstract: New Isoprenylated Aurones from the Flowers of Rosa damascena. Issue 35 (2nd September 2014) - Li, Yin‐Ke; Sun, Ji‐Qing; Gao, Xue‐Mei; Lei, Chun
Abstract isolation and structure elucidation of three new isoprenylated aurones, damaurones C—E, along with six known compounds